Dampak Pernikahan Dini Terhadap Kesehatan Reproduksi Dan Psikologi Pada Remaja Putri - Vivin Indrianita; Januar Dwi Christy; Hidayatun Nufus (Fakultas Ilmu Kesehatan Universitas Merdeka Surabaya, 2025)
Early marriage is a marriage conducted by someone who is relatively young, namely between the ages of 10 - 19 years. There are many factors that cause early marriage to still exist in some regions, including economic factors, knowledge, customs/culture, education, free sex, and pregnancy out of wedlock. This remains a serious problem that causes many adverse impacts. The disadvantages affect women more, both physically, psychologically, economically, in terms of autonomy, and education. At a very young age, a girl's body is not fully mature physically and mentally, so early marriage can lead to serious reproductive health complications. The purpose of this research is to measure the knowledge of adolescent girls regarding the impact of early marriage on reproductive health and psychology in the West Surabaya area. This research uses a pre-experimental method with a one-group pre-test and post-test design approach. The test was administered twice to the group that had received counseling, without a control group. Statistical analysis was conducted using the t-test. The level of knowledge of adolescents in the western Surabaya area about the impacts of early marriage before receiving health counseling was considered moderate, with a percentage of 50%. After receiving health counseling, the adolescents' level of knowledge increased to good, with a percentage of 59.3%. This indicates that providing health counseling has a significant effect on adolescents' knowledge about the impacts of early marriage on reproductive and psychological health, as shown by a p-value of 0.003.